Supply Chain Managment Local Sheep : Fat Tailed Sheep in Jember Indonesia During and After Eid Adha - Hasanah, Niswatin; Subagja, Hariadi; Wahyono, Nanang Dwi (Universitas Halu Oleo, 2022)
The Aims of this research are to; 1) know the supply chain of fat-tailed sheep with institutions involved in marketing in Gumukmas District, Jember Regency. 2) find out the difference in the price of fat tail sheep in Gumukmas District, Jember Regency. This research was conducted in May-August 2021 in Gumukmas District, Jember Regency. The data obtained were analyzed descriptively by calculating the formula for marketing margin, margin percentage, and marketing efficiency. The results showed that the most efficient supply chain during the Eid al-Adha period in Gumukmas District, Jember Regency, male and female sheep tails were pattern I in terms of farmer price share, males 95.24% and females 92.29%. The efficiency of the supply chain after Eid al-Adha male fat-tailed sheep is a pattern I with a farmer price share of 88.00% and a female in pattern III with a farmer price share of 90.17%.